The Efficacy and Safety of Percutaneous Cystolithotripsy for Vesical Calculus in Children: A Single-Center Study - Khan, Mohammad Kamran; Hassan, Asiya; Hanif, Mohammad; Alam, Gohar; Ali, Liaqat; Naveed, Mohammad; Ullah, Ihsan (American Journal of Health, Medicine and Nursing Practice, 2022)
Purpose: The study aimed to assess the outcome and safety of PCCL in the pediatric population coming with bladder stones in developing countries. Methodology: Patients of pediatric age with vesical calculus were evaluated for PCCL. Department of Peads Urology Institute of Kidney Diseases Thirty participants were included in the single center study, with enrollment beginning in January 2000 and ending in August 2021. General anesthesia was used for the operation. Following a cystoscopy examination, a suprapubic puncture was performed, and the urethral tract was dilated to a maximum of 26 Fr. Pneumatic lithotripsy was used to break up the stone. A nephroscope was used to see where it was lodged so it could be removed. A percutaneous urethral catheter was inserted was taken out after 48 postoperative hours. Findings: The patients' median age was 4.1 (1-10). Patients tended to be men. The typical size of a gem was 10.1 millimeters. The average operational time to successfully remove the stones was just 30 minutes. Hematuria, infection, and mild mucosal damage were the only serious complications seen during or after surgery, and all were treated conservatively. Ammonium acid urate comprised the bulk of the stones and the nucleus in 26 cases (86%). Percutaneous suprapubic lithotripsy is a tested and reliable method with a high success rate for treating bladder stones in children. The procedure is short and has few adverse effects.